PENGARUH INTENSITAS MEMBACA AL-QUR’AN TERHADAP KECERDASAN SPIRITUAL SANTRI PONDOK PESANTREN HUBBUL QUR’AN DIWEK JOMBANG - AB, M. Jalal; Arifin Hasan, Zaenal; uje, jumari (EL-Islam, 2024)
This study aims determine the influence of the intensity of reading the Qur'an on the spiritual intelligence of students of the Hubbul Qur'an Islamic Boarding School in Diwek Jombang. This research was conducted from March 26 to April 7, 2023, at the Hubbul Qur'an Islamic Boarding School in Diwek Jombang. The type of research used in this study is facto-experimental research aimed at finding causes that allow changes behavior, symptoms, or phenomena caused by an event, behavior, or things that cause changes in the independent variable as a whole to occur.The results showed that the intensity of reading the Qur'an affected the spiritual intelligence of Hubbul Qur'an students in Jombang. This is evidenced based on the calculation results of the SPSS output above, which show that the value of the correlation coefficient between the intensity of reading the Qur'an and spiritual intelligence is rcalculate = 0.558, while Rtabel = 0.254. Because rcalculate is greater than Rtabel, this means that the two variables have a level of relationship. In the Sig. (2-tailed) column of 0.000 < 0.05, H0 is rejected and Ha is accepted, meaning that the that there is a positive and significant relationship between the intensity of reading the Qur'an and the spiritual intelligence of students of Hubbul Qur'an Islamic Boarding School Diwek Jombang by 31.2%, while the remaining 68.8% is caused by other factors.